2015
DOI: 10.1186/s12986-015-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid/chromium supplement rescues diet-induced insulin resistance and obesity in mice

Abstract: Abdominal obesity is a major risk factor for insulin resistance, type 2 diabetes and cardiovascular diseases. Dietary fat induces insulin resistance in humans and rodents. The current study investigates whether a Chlorogenic acid/Chromium III supplement rescues obesity and insulin resistance caused by high-fat feeding of male C57BL/6 J mice for 7 weeks. Administering an oral daily dose of this supplement in the last 3 weeks of feeding reversed diet-induced body weight gain and insulin resistance, assessed by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 44 publications
2
12
0
1
Order By: Relevance
“…CGA also exhibits anti‐inflammatory, antitumor, and immunomodulatory properties (Liang & Kitts, ; Xu, Hu, & Liu, ). Moreover, it has been determined that CGA can improve insulin resistance and prevent diet‐induced obesity (Ghadieh et al., ; Ma, Gao, & Liu, ). Studies have shown that a high‐fat diet supplemented with CGA at 0.02% (m/m) improves body weight, lipid metabolism, and obesity‐related hormones levels in mice fed with a high fat (Cho et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…CGA also exhibits anti‐inflammatory, antitumor, and immunomodulatory properties (Liang & Kitts, ; Xu, Hu, & Liu, ). Moreover, it has been determined that CGA can improve insulin resistance and prevent diet‐induced obesity (Ghadieh et al., ; Ma, Gao, & Liu, ). Studies have shown that a high‐fat diet supplemented with CGA at 0.02% (m/m) improves body weight, lipid metabolism, and obesity‐related hormones levels in mice fed with a high fat (Cho et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies demonstrated that chlorogenic acid (CGA), a type of dietary polyphenol present in high quantities in plants and constituting the main active ingredient in many fruits, vegetables, and plants [16, 17], possesses numerous pharmacological activities, including those associated with antioxidative [18], anticancer [1921], hypolipidemic [22], antihypertensive [23], anti-inflammatory [24], and hypoglycemic effects. Moreover, studies reported effects related to anti-insulin resistance and obesity [25], and protection against plant pathogenic fungi [26], as well as antimicrobial effects [27], inhibition of bile-duct ligation-induced liver injury [28], and attenuation of lipopolysaccharide-induced acute kidney injury [29]. Furthermore, CGA reportedly exhibits neuroprotective activity [30], and hypoxia-induced angiogenesis [31], and extends the lifespan of Caenorhabditis elegans [32].…”
Section: Introductionmentioning
confidence: 99%
“…In human trials, an increase in energy expenditure has been reported, varying from 6% (after 50 mg caffeine intake) [58] to 7% (after 200 mg caffeine consumption) [57]. Chlorogenic acid has been reported to have beneficial effects against obesity and other dysmetabolic disorders, as well as playing a favorable role in energetic metabolism in both human and animal studies [59,60]. In a pilot study, the consumption of 1 cup of green coffee (containing 6 mg caffeine per kg of lean body mass, about 215-280 mg) determined an increase of REE by 6.4% at 30 min and 2.2% at 180 min, with a positive correlation between the chlorogenic acid assumed and the REE values at 30 min [61].…”
Section: Green Coffee Available Evidencementioning
confidence: 99%